Productivity Improvement Based on Lean and Green Productivity in Herbal Tea Production Line CV. DM - Damayanti, Dana; Suharno, Suharno; Ainuri, Makhmudun (agriTECH, 2024)
Herbal tea is a functional beverage with significant health benefits, produced from processed plants, namely Chinese teak (Cassia angustifolia Vahl) and soursop leaves (Annona muricata L). However, herbal industry faces a productivity problem due to the production process time caused by human factors, machines, and raw materials. Productivity can also be affected by non-value-adding activities in the production processes, such as unnecessary inventory and overproduction. Fossil energy used by industry to generate electricity contributes to the production of solid waste, posing a long-term environmental risk. To address this problem, Objective Matrix (OMAX) is needed to measure the industry production rate, where all non-value-adding activities are reduced in lean and green productivity. The concept of lean and green productivity facilitates the identification of all activities to determine the locus of the highest waste, material, or energy usage. Therefore, this research aimed to propose alternative improvements for enhanced productivity by assessing production rates and identifying generated waste, energy consumption, and emissions. The results show that herbal industry had low productivity, 0.4, on a scale of 1. To improve efficiency, recommendations for lean aspect were based on forecast demand and workload. This improvement was projected to raise Process Cycle Efficiency (PCE) ore from 7.97% to 9.05% and reduce solid waste by maintaining and repairing filling machines. Green aspect could be improved by turning off idle facilities and machines, thereby minimizing electricity energy usage to 43.37%.